2021
DOI: 10.1155/2021/5518750
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the Mechanism of Principal Drugs of Lianpu Drink on Chronic Gastritis by Network Pharmacology

Abstract: Lianpu drink (LPD) is a traditional Chinese medicine (TCM) formula for the treatment of chronic gastritis (CG), and its clinical effects have been effectively verified. However, due to the complexity of the chemical composition of TCM formulas, its mechanism of action has not yet been clearly explained. Many studies have shown that the principal drugs in the TCM formula play a major therapeutic role. Therefore, in this study, the principal drugs Coptidis Rhizoma (CR) and Magnolia officinalis Rehd. et Wils. (MO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Zhou et al confirmed that the commonly used formula Lianpu Drink, primarily composed of Coptis chinensis and Magnolia officinalis , alleviated chronic gastritis symptoms by constructing the “compound–target–disease” network and screening common targets. They confirmed through animal experiments that Lianpu Drink played its role through the RIP/P38 pathway and inhibition of MKK6/P38 ( Zhou, et al, 2021a ).…”
Section: Application Of Network Pharmacology In Digestive Diseasesmentioning
confidence: 80%
“…Zhou et al confirmed that the commonly used formula Lianpu Drink, primarily composed of Coptis chinensis and Magnolia officinalis , alleviated chronic gastritis symptoms by constructing the “compound–target–disease” network and screening common targets. They confirmed through animal experiments that Lianpu Drink played its role through the RIP/P38 pathway and inhibition of MKK6/P38 ( Zhou, et al, 2021a ).…”
Section: Application Of Network Pharmacology In Digestive Diseasesmentioning
confidence: 80%